Economic Evaluation of Five Tobacco Control Policies Across Seven European Countries. Issue 7 (27th July 2019) - Leão, Teresa; Perelman, Julian; Clancy, Luke; Mlinarić, Martin; Kinnunen, Jaana M; Nuyts, Paulien A W; Mélard, Nora; Rimpelä, Arja; Lorant, Vincent; Kunst, Anton E
Abstract: Introduction: Economic evaluations of tobacco control policies targeting adolescents are scarce. Few take into account real-world, large-scale implementation costs; few compare cost-effectiveness of different policies across different countries. We assessed the cost-effectiveness of five tobacco control policies (nonschool bans, including bans on sales to minors, bans on smoking in public places, bans on advertising at points-of-sale, school smoke-free bans, and school education programs), implemented in 2016 in Finland, Ireland, the Netherlands, Belgium, Germany, Italy, and Portugal. Methods: Cost-effectiveness estimates were calculated per country and per policy, from the State perspective. Costs were collected by combining quantitative questionnaires with semi-structured interviews on how policies were implemented in each setting, in real practice. Short-term effectiveness was based on the literature, and long-term effectiveness was modeled using the DYNAMO-HIA tool. Discount rates of 3.5% were used for costs and effectiveness. Sensitivity analyses considered 1%–50% short-term effectiveness estimates, highest cost estimates, and undiscounted effectiveness. Findings: Nonschool bans cost up to €253.23 per healthy life year, school smoking bans up to €91.87 per healthy life year, and school education programs up to €481.35 per healthy life year. Cost-effectiveness depended on the costs of implementation, short-term effectiveness, initial smoking rates, dimension of the target population, and weight of smoking in overall mortality and morbidity. Conclusions: All five policies were highly cost-effective in all countries according to the World Health Organization thresholds for public health interventions. Cost-effectiveness was preserved even when using the highest costs and most conservative effectiveness estimates. Implications: Economic evaluations using real-world data on tobacco control policies implemented at a large scale are scarce, especially considering nonschool bans targeting adolescents. We assessed the cost-effectiveness of five tobacco control policies implemented in 2016 in Finland, Ireland, the Netherlands, Belgium, Germany, Italy, and Portugal. This study shows that all five policies were highly cost-effective considering the World Health Organization threshold, even when considering the highest costs and most conservative effectiveness estimates.